COLIFORM BACTERIA CONTAMINATION TEST IN PACKAGED TEA DRINKS SOLD IN JEMBATAN MERAH STREET, CONDONGCATUR, SLEMAN USING MPN METHOD - Purwanti, Ratih; Rege, Feblin Wini; Rizki, Cut Novrita (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2025)
Iced tea is a popular drink that is most in demand because of its sweet and refreshing cold taste. However, iced tea contaminated with bacteria can cause illness to consumer. Coliform bacteria are bacteria that contaminate many foods and drinks. These bacteria can contaminate food or drinks through soil, dust, insects, animal feces, and water. This study aims to determine the results of coliform bacteria contamination tests on packaged iced tea drinks sold in the Jalan Jembatan Merah area, Condongcatur, Sleman. This study is a descriptive study. Samples of 5 packaged iced tea drinks were tested for bacterial contamination using the MPN method variety 3.3.3. through three stages of testing, namely, predictive test, confirmatory test, and complementary test. The results of the predictive test obtained 4 iced tea samples positive for coliform. In the confirmatory test, there were 2 iced tea samples that were positive for coliform bacteria contamination, namely sample B with an MPN index value of 6/100 mL and sample D with an MPN index value of 3/100 mL. In the complementary test, sample B was found to be contaminated by Enterobacter bacteria and sample D was contaminated with Escherichia coli.